The Influence of Spiritual Well-Being on Consumer Materialism: An Empirical Study from Turkey (European Journal of Marketing and Economics, 2026)
Purpose: This study aims to investigate the relationship between spiritual well-being and materialism among consumers in Turkey, contributing to marketing literature and offering insights for developing effective marketing strategies. Design/methodology/approach: Data were collected in 2018 through an online survey from 1243 individuals aged 18 and above residing in Turkey. Spiritual well-being was measured using a 29-item scale with three sub-dimensions (transcendence, harmony with nature, and anomie), validated by Ekşi and Kardaş (2017). Materialism was assessed using a 6-item scale, validated by Richins (2004) and translated into Turkish by Tiltay (2014). The Cronbach's alpha coefficients were 0.890 for spiritual well-being and 0.767 for materialism, indicating good reliability. Findings: The results reveal that spiritual well-being significantly, albeit weakly, explains materialistic attitudes. Unexpectedly, transcendence and anomie, sub-dimensions of spiritual well-being, exhibited a positive (rather than negative) relationship with materialistic attitudes. Anomie was identified as the strongest predictor of materialistic attitudes. Conversely, harmony with nature showed no significant relationship with materialistic attitudes. Practical implications: The findings suggest that marketers should consider the complex interplay between spiritual beliefs and consumer materialism when formulating strategies, particularly in contexts like Turkey where specific spiritual dimensions may surprisingly correlate with materialistic tendencies.
Keywords: Spiritual Well-Being, Consumer Materialism, Consumer Behavior, Transcendence, Anomie, Turkey